2017
DOI: 10.7150/jca.19181
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective discussion of the prognostic value of combining prothrombin time(PT) and fibrinogen(Fbg) in patients with Hepatocellular carcinoma

Abstract: Aims: The levels of coagulation system tests have been studied in various cancers. In this study, our aim is to evaluate the prognostic value of pretreatment plasma coagulation tests in hepatocellular carcinoma (HCC) patients. Patient and methods: A retrospective study was performed in 539 patients with HCC, and follow-up period was at least 60 months until recurrence or death. The prognostic significance of coagulation system tests (prothrombin time, activated partial thromboplastin time, thrombin time, fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…This is in accordance with the findings of Xue-Ping Wang et al [9] . Platelet count was normal in all cases of liver SOL in present study as opposed to 46.01% observed in Xue-Ping Wang et al [9] . This difference may be due to the difference in total study population.…”
Section: Discussionsupporting
confidence: 83%
“…This is in accordance with the findings of Xue-Ping Wang et al [9] . Platelet count was normal in all cases of liver SOL in present study as opposed to 46.01% observed in Xue-Ping Wang et al [9] . This difference may be due to the difference in total study population.…”
Section: Discussionsupporting
confidence: 83%
“…Surgical resection remains the initial treatment of choice for most of early stage HCC patients because it is likely to yield a better prognosis than radiofrequency ablation (RFA) treatment 5 , 6 . Previous studies have elucidated the factors that influence the prognosis of postoperative HCC patients 7 - 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The current prognostic models for HCC include parameters related to HCC, such as the tumour diameter, tumour number, presence of vascular invasion, and extent of tumour differentiation and lymph node metastasis 7 , 8 . Previous studies have reported that there is a significantly different prognosis between early HCC patients within the Milan criteria and cases beyond this criterion 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence demonstrated that prolonged PT was associated with poor prognosis in lung cancer [16,17], pancreatic cancer [18], colorectal cancer [19], and hepatocellular carcinoma [20]. The exact mechanisms underlying this association remain unclear.…”
Section: Subclinical Hypercoagulation Condition Is Common In Cancer Pmentioning
confidence: 99%